PENERAPAN TEKNOLOGI TEPAT GUNA UNTUK MENINGKATKAN KAPASITAS PRODUKSI KUE KARAH PADA UMKM DI DESA LANGUNG KECAMATAN MEUREUBO - Fitriadi Fitriadi; Muzakir Muzakir; Arie Saputra; Nissa Prasanti; Khairul Hadi; Iing Pamungkas; Heri Tri Irawan (Universitas Teuku Umar, 2020)
Kue Karah is a traditional cake that has been part of the cultural richness of the Acehnese people for a long time. In West Aceh district, the center of Kue Karah production is in Meureubo District, especially in Langung Village. The problem of partners in making Kue Karah is the process of making karah cakes in the traditional way. In the manufacturing process workers experience the risk of fatigue, and musculoskeletal disorders caused by exposure to heat production equipment. In addition, the quality of products produced is not standardized and organizational and financial management is still family based. For this reason, it is necessary to apply the right technology to overcome this weakness. This community service program is a community partnership program between the university and UMKM makers Kue Karah. This program not only offers problem solving regarding the use of Kue Karah makers, but also technology transfer in the form of Kue Karah makers to improve the quality of Kue Karah products and increase production volumes. In addition, this service program also provides training and assistance in organizational and financial management. Thus this program has a comprehensive, meaningful, complete and sustainable value.